2012
DOI: 10.1159/000337031
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Expressions of MMP-9, TIMP-1 and PAI-1 in Patients Undergoing Surgery for Clinically Suspected Appendicitis

Abstract: Background/Aims: To examine, compare and correlate the expressions of matrix metalloproteinase 9 (MMP-9), tissue inhibitor of metalloproteinase 1 (TIMP-1) and plasminogen activator inhibitor type 1 (PAI-1) in appendiceal tissue and pre- and postoperative blood samples in patients undergoing surgery for clinically suspected appendicitis. Methods: Fifty-seven patients with complete tissue and blood samples were included and divided into groups of noninflamed appendix/lymphadenitis (n = 7), phlegmonous appendicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 91 publications
(69 reference statements)
0
1
0
5
Order By: Relevance
“…It is the primary physiological inhibitor of the urokinase-plasminogen activator (uPA) and tissue-plasminogen activator (tPA) systems ( 43 ). The fibrinolytic system, which includes uPA and tPA systems, is the key to regulating the activity of matrix metalloproteinases (MMPs) and ECM degradation factors ( 42 , 44 ). Previous studies have demonstrated that overexpression of PAI-1 can induce fibrosis in many organs, especially in liver, where it can lead to hepatocellular carcinoma ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is the primary physiological inhibitor of the urokinase-plasminogen activator (uPA) and tissue-plasminogen activator (tPA) systems ( 43 ). The fibrinolytic system, which includes uPA and tPA systems, is the key to regulating the activity of matrix metalloproteinases (MMPs) and ECM degradation factors ( 42 , 44 ). Previous studies have demonstrated that overexpression of PAI-1 can induce fibrosis in many organs, especially in liver, where it can lead to hepatocellular carcinoma ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 memiliki peningkatan paling signifikan dan paling tinggi pada gangrenous appendicitis dan perforated appendicitis. [14] Gambar 4. Ekspresi MMP-9 pada Berbagai Komplikasi Apendisitis [14] Masing-masing komplikasi apendisitis memiliki peningkatan sangat signfikan pada ekspresi MMP-9.…”
Section: Mmp Pada Berbagai Komplikasi Apendisitis Akutunclassified
“…[14] Gambar 4. Ekspresi MMP-9 pada Berbagai Komplikasi Apendisitis [14] Masing-masing komplikasi apendisitis memiliki peningkatan sangat signfikan pada ekspresi MMP-9. Gangrenous appendicitis memiliki nilai MMP tertinggi.…”
Section: Mmp Pada Berbagai Komplikasi Apendisitis Akutunclassified
See 2 more Smart Citations